2018
DOI: 10.1002/jccs.201800099
|View full text |Cite
|
Sign up to set email alerts
|

Research on the oxygen reduction reaction (ORR) mechanism of g‐C3N4 doped by Ag based on first‐principles calculations

Abstract: Developing non‐platinum composite catalysts has become a hot research topic for the oxygen reduction reaction (ORR). In this study, Ag/g‐C3N4 (the mass ratio of Ag and g‐C3N4 = 3%) catalysts were prepared through a photoreduction method. The catalytic performance of g‐C3N4 was greatly enhanced after Ag doping. The current density of Ag/g‐C3N4 was −21 μA/mm2, which is 3 times that of pure g‐C3N4. The mechanism of ORR activity enhancement is discussed based on first‐principles calculation. Ag, as the active site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For evaluation of the solvent effect, the model reaction was investigated by applying various solvents (including EtOH, H 2 O, MeOH, CH 3 CN, toluene) and in solvent-free conditions (Table 1, entries [8][9][10][11][12].The results revealed that, in the presence of both types of protic and aprotic solvents, only a trace amount of product was obtained and the best result was achieved in the absence of solvent. In continuance, the influence of temperature was investigated (Table 1, entries [13][14][15][16][17]. Relying on the obtained results, as the temperature was conducted to 100 °C, the desired product was formed at a shorter reaction time and the yield increased to 87% (Table 1, entry 17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For evaluation of the solvent effect, the model reaction was investigated by applying various solvents (including EtOH, H 2 O, MeOH, CH 3 CN, toluene) and in solvent-free conditions (Table 1, entries [8][9][10][11][12].The results revealed that, in the presence of both types of protic and aprotic solvents, only a trace amount of product was obtained and the best result was achieved in the absence of solvent. In continuance, the influence of temperature was investigated (Table 1, entries [13][14][15][16][17]. Relying on the obtained results, as the temperature was conducted to 100 °C, the desired product was formed at a shorter reaction time and the yield increased to 87% (Table 1, entry 17).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, g-C 3 N 4 substructure, based on aromatic C-N heterocycles and optimized van der Waals forces between its two-dimensional conjugated planes, can be prepared by polymerization of affordable nitrogen-containing materials like melamine, urea, cyanamide, thiourea, and dicyandiamide [6]. Reasonable physical and chemical property, unique electronic property, exclusive thermal and chemical resistance, and high specific surface area [7] make this material be applied in many scientific fields such as fuel cell [8], sensor [9], solar cell [10], metal-free catalyst [11], heterogeneous photocatalyst [12], energy storage [13], oxygen reduction reaction (ORR) [14], hydrogen evolution [15], photocatalytic degradation of pollutants [16,17], and oxidation [18]. The preparation of wellordered mesoporous g-C 3 N 4 leads to higher specific surface area, stronger adsorption capacity, and larger pore volume and increases active chemical sites, thereby enhancing the performance of g-C 3 N 4 as an efficient catalyst and catalyst support [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, g-C 3 N 4 is a kind of effectively modified material semiconductor photocatalysts, many strategies had been proposed to promote the photocatalytic performance of g-C 3 N 4 such as doping with metal elements (K, Na, Fe, Ag, Au, Cu, In, Bi, Mn, Co, etc. ), [19][20][21][22][23][24] free-metal elements (C, P, S, Si, O, etc. ), [25][26][27] metal oxide (ZnO, TiO 2 , Fe 2 O 3 , CuO, Bi 2 O 3 , CeO 2 , WO 3 , Ag 2 O etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Finally, combined fuel cells, known as fuel piles, have wide applications in a variety of fields, such as space crafts, reconnaissance drones, discovery submarines, hybrid cars, and fuel pile power plants. [3][4][5][6][7][8][9] In contrast with these advantages, the major problem with fuel cells is that the cell's reaction rate is typically low and virtually useless under normal conditions. Thus, since the introduction of fuel cells, many researchers, including Denaley et al, have tried to find the effective ways to enhance the fuel cells' reaction rate.…”
Section: Introductionmentioning
confidence: 99%